Investigation of The Roles of Hydrogen Peroxide and NADPH Oxidase in The Regulation of Polyamine Metabolism in Maize Plants under Drought Stress Conditions - Aykut Sağlam; Mehmet Demiralay; Fuat Yetişsin; Asım Kadıoğlu (Journal of Agricultural Sciences)
The relationship between hydrogen peroxide and the metabolism of polyamines and the role of NADPH oxidase (NOX) in that relationship under drought conditions remains unclear. To reveal the relationship, expression levels of the genes in polyamine metabolism, such as arginine decarboxylase, agmatine aminohydrolase, spermidine synthase, S-adenosyl methionine decarboxylase, diamine oxidase, and polyamine oxidase were determined by RT PCR under drought stress combined with exogenous hydrogen peroxide (H2O2) and diphenyleneiodonium chloride (DPI) treatments in maize seedlings. In addition, some basic stress parameters (leaf water potential, lipid peroxidation), levels of polyamines (putrescine, spermidine, and spermine), and gene expression of NOX were measured under drought stress. Exogenous H2O2 induced the polyamine content by up-regulating polyamine-synthesizing genes and downregulating polyamine oxidizing genes. When the NOX enzyme was inhibited by DPI, the polyamine pathway tended towards degradation instead of production. Exogenous H2O2 regulated the metabolism of polyamines to promote their synthesis, and NOX played a key role in that regulation.